Mechanisms of PDL1-mediated regulation of autoimmune diabetes - Guleria, Indira (Clinical immunology (Orlando, Fla.), 2007)
The PD-1-PDL1 pathway plays a critical role in regulating autoimmune diabetes as blockade or deficiency of PD-1 or PDL1 results in accelerated disease in NOD mice. We explored the cellular mechanisms involved in the regulation of these autoimmune responses by investigations involving various gene-deficient mice on the NOD background. Administration of blocking anti-PDL1 antibody to CD4+ T cell-deficient, CD8+ T cell-deficient and B cell-deficient mice demonstrated that PDL1-mediated regulation of autoreactive CD4+ and CD8+ T cells is critical for diabetes development. This concept was confirmed by adoptive transfer studies utilizing lymphocytes from BDC2.5 and 4.1 (CD4+) TCR transgenic mice and 8.3 (CD8+) TCR transgenic mice; efforts showing increased proliferation of both CD4+ and CD8+ T cells following PDL1 blockade in vivo. Furthermore, we observed that anti-PDL1-mediated acceleration is dependent upon events occurring in the pancreatic lymph nodes during early disease stages, but becomes independent of the pancreatic lymph nodes during later disease stages. These data provide strong evidence that PDL1 regulates autoimmune diabetes by limiting the expansion of CD4+ and CD8+ autoreactive T cells, and define the timing and locale of PDL1-mediated regulation of type 1 diabetes